Food security: focus on agriculture - Porter, J.R.; Challinor, Andrew J.; Ewert, Frank; Falloon, Pete D.; Fischer T; Gregory P; Ittersum, Martin K. van; Olesen, Jørgen E.; Moore KJ; Rosenzweig, Cynthia; Smith, Pete (American Association for the Advancement of Science, 2010)
The review by H. C. J. Godfray et al. (12 February, p. 812) and the rest of the special section on Food Security call for a multifaceted approach to future global food security. We would like to emphasize three agricultural issues that were lacking